Turn-Over Guru pada Madrasah Aliyah Nahdlatul Ulama - Mochamad Iskarim (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2016)
The aims of this research were to know the positive and negative impact of teacher turn over at Madrasah Aliyah Nahdlatul Ulama Banyuputih Kabupaten Batang. This research was use analytical descriptive qualitative approach with depth interview, questionnaire and documentation as data collection methods. The results of this research shows that the positive impact occur more than the negative impact when there was teacher turn over; and the presence of a new teacher become student’s favourite on creativity, learning innovation, and motivation aspects.